(untitled) (Literasi Nusantara, 2022)
The purpose of this study was to develop a valid, interesting, and effective narrative text enrichment book of the Bangkalan historical tour for elementary school students. Bangkalan is one of the regencies on the island of Madura. Many tourist attractions in Bangkalan have historical narrative stories. This research is research development (Research and Development) by modifying the ten steps into nine steps. All stages in the nine steps of this research adequately represent the initial activities to the end of the activities which are known to be research results based on the context of this research. The nine steps include theoretical and practical analysis, planning, development of product drafts, initial product validation tests, revision of validation test results, limited trials, limited trial revisions, field trials, and product improvement. The test subjects in this study were elementary school students in Bangkalan.